TALENT MANAGEMENT IN EDUCATION: DEVELOPING TEACHER COMPETENCE IN THE DIGITAL ERA - Melania, Melania; Yulianah, Yulianah (Universitas Indraprasta PGRI, 2024)
The increasingly rapid digital transformation requires teachers to have relevant and adaptive skills in utilizing technology as part of the learning process. Talent management plays an important role in ensuring continuous competency development for teachers through various training programs, career development, and performance evaluation. This study aims to analyze talent management in education, especially related to the development of teacher competencies in the digital era. This study uses a qualitative approach with a descriptive method. The results of the study indicate that talent management plays an important role in developing teacher competencies in the digital era with a focus on talent identification, training, mentoring, technology utilization, and performance evaluation. This process not only improves teachers' teaching skills but also encourages innovation and collaboration in the educational environment. With the right support and constructive feedback, talent management creates a positive school culture, where teachers feel valued and motivated to develop. Despite challenges such as limited resources, successful talent management can significantly improve the quality of education and help teachers adapt to changing times. Overall, investment in talent management contributes to achieving a better vision of education in a competitive global context.